Fuelwood revisited: what has changed in the last decade? - Arnold, J.E.M.; Kohlin, G.; Persson, R.; Shepherd, G. (Center for International Forestry Research, 2003)
The impact of woodfuel collection on forests has been controversial and its role in rural livelihoods and deforestation the subject of considerable debate. This study reviews the main dimensions of this discourse and the resulting responses from the forestry sector. It assesses new information that has come to light over the past decade, looking at national and global trends in woodfuel production and use and the evolution of patterns of urban and rural demand and supply. It examines livelihood and environmental dimensions of relevance to forestry and outlines some of the main issues that warrant additional attention. It is thus intended more as a foundation for further discussion, rather than being a set of prescriptions for action by forestry, though where these are evident they are identified.